Mycobacteriosis in patients with breast implants: a case review from the Ivo Pitanguy Institute Micobacteriose em implantes mamários: revisão da casuística do Instituto Ivo Pitanguy - Gabrielle Bessa Wajnberg; Vinicius Volpe D'Angieri Basile; Luís Gustavo Moraes Prado; José de Faria; Henrique N Radwanski; Ivo Pitanguy (Revista Brasileira de Cirurgia Plástica, 2011)
INTRODUCTION: Reports of infections caused by rapidly growing mycobacteria during plastic surgery have increased in recent years despite improvements in techniques of asepsis/antisepsis and antibiotic prophylaxis. Infections occurring after the insertion of breast implants are a cause of patient morbidity and a significant problem for the surgeon. METHODS: Breast implant surgery cases complicated by mycobacterial infections at the Infirmary ward 38th of the Santa Casa da Misericórdia, Rio de Janeiro were retrospectively reviewed. A description of the current guidelines for the prevention and treatment of mycobacteriosis is included. Laboratory confirmed and clinically suspected cases were included in this study. RESULTS: Of 483 augmentation mammaplasty cases, 3 patients developed mycobacterial infections in the last 3 years. In 2 patients, there was a suspicion of infection that was not confirmed by laboratory data. CONCLUSIONS: Prophylaxis is fundamental for reducing the incidence of mycobacteriosis during plastic surgery procedures. However, the identification, diagnosis, and treatment of mycobacterial diseases are important to minimize the morbidity of this type of infection INTRODUÇÃO: Nos últimos anos, foram crescentes os registros de infecções por micobactéria de crescimento rápido em cirurgia plástica, mesmo com a melhoria dos métodos de assepsia/ antissepsia e da antibioticoprofilaxia. A infecção após inclusão de implantes mamários causa grande morbidade às pacientes e transtorno ao cirurgião. MÉTODO: Estudo retrospectivo dos casos de infecção por micobactéria de crescimento rápido da 38ª Enfermaria da Santa Casa da Misericórdia do Rio de Janeiro, após inclusão de implantes mamários, em que são apresentadas propostas de prevenção e tratamento da micobacteriose. Foram incluídos os casos confirmados laboratorialmente e os clinicamente suspeitos. RESULTADOS: Até o presente momento foram confirmados 3 casos de infecção por micobactéria, num total de 483 mamaplastia de aumento no decorrer de 3 anos. Em 2 pacientes, houve suspeita de infecção, porém sem confirmação laboratorial. CONCLUSÕES: A profilaxia é o pilar fundamental para a redução do impacto da micobacteriose em procedimentos de cirurgia plástica. Entretanto, saber identificar, diagnosticar e tratar corretamente a micobacteriose é de suma importância para minimizar a morbidade da paciente